Glasovno zavedanje v prvem razredu - Brumen, Dušanka (Revija za elementarno izobraževanje, 2012)
Phonemic Awareness in the First Grade of Primary School. The development of literacy starts already in the pre-school period on an informal basis, and it formally and systematically continues into primary school until the end of the third grade. Phonemic awareness plays a key role in this, being developed throughout the pre-school period as well as in the first three years of primary schooling, particularly in the first grade. As regards the development of phonemic awareness, we have to consider also the development of auditory awareness in relation to the length of words and the number of words in a sentence, auditory discrimination and distinction, as well as finding and creating rhymes. This article presents the results of a two-year research on literacy development in children, or to be more specific, on children's phonemic awareness and auditory discrimination as well as the influence of the latter on pronouncing sounds and on the orthographic correctness in dictation exercises.
Keywords: listening; discriminating and distinctive listening; stimulating phonemic awareness; correlation; dictation; first grade; second grade